Epicardial Echocardiography as Rescue Modality for Detection of Dynamic Right Ventricular Outflow Tract Obstruction in Post Pulmonary Valve Stenosis Repair. Issue 10 (15th November 2019) - Munirathinam, Ganesh Kumar; Kajal, Kamal; Jayant, Aveek; Dogra, Neeti; Singh, Harkant
Abstract : Supplemental Digital Content is available in the text.